2004
DOI: 10.1002/chem.200305447
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Conjugation Leading to Bathochromic or Hypsochromic Effects in OPV Series

Abstract: Four OPV series 1-4 (a-d) with a terminal dialkylamino group as electron donor were prepared by Wittig-Horner reactions. To study the influence of the push-pull effect on the long-wavelength absorption, three of the four series contained terminal acceptor groups (CN, CHO, NO(2)). The length of the chromophores strongly affects the intramolecular charge transfer (ICT)-an effect which superimposes upon the extension of the conjugation. Increasing numbers n of repeat units cause an overall bathochromic shift for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 67 publications
4
71
0
5
Order By: Relevance
“…Computational studies actually revealed that within this series of constitutional isomers, the variance in the lowest-energy transitions is caused by differences in the HOMO (highest occupied molecular orbital) energy, which is highest in the cross-conjugated system. It became apparent, therefore, in this investigation that the correlation between the position of λ max in the UV/vis spectra and the effectiveness of different conjugation pathways is not always valid; a conclusion also reached by others [51,52]. For compounds with strong donor and acceptor moieties, the λ max in the UV/vis spectrum should only be considered as a measure of the change of the degree of CT in the transition from the ground state to the excited state, and should not be used for the study of conjugation effectiveness.…”
Section: © 2005 Iupac Pure and Applied Chemistry 77 1851-1863mentioning
confidence: 49%
“…Computational studies actually revealed that within this series of constitutional isomers, the variance in the lowest-energy transitions is caused by differences in the HOMO (highest occupied molecular orbital) energy, which is highest in the cross-conjugated system. It became apparent, therefore, in this investigation that the correlation between the position of λ max in the UV/vis spectra and the effectiveness of different conjugation pathways is not always valid; a conclusion also reached by others [51,52]. For compounds with strong donor and acceptor moieties, the λ max in the UV/vis spectrum should only be considered as a measure of the change of the degree of CT in the transition from the ground state to the excited state, and should not be used for the study of conjugation effectiveness.…”
Section: © 2005 Iupac Pure and Applied Chemistry 77 1851-1863mentioning
confidence: 49%
“…In this work, we show along with other investigators 3,8,[10][11][12][13][14][15]25 , that the overall response of the properties of π-conjugated compounds to donor-acceptor substitution can be expressed by means of simple analytical expressions. In earlier work 27 , we also showed that part of the response of a given property can be ascribed to substituent cooperative effects, i.e.…”
Section: The Substituent Cooperative Effect On the Propertiesmentioning
confidence: 65%
“…Concepts such as Effective Conjugation Length (ECL) 8 , Confinement Length (CL) 9 or Delocalisation Length (DL) 9 , which address the issues related to the saturation of a particular property with respect to the conjugation length, emerged. At the same time, Quantitative Structure-Property Relationships (QSPR) that model the dependence of molecular properties on chain size and substitution pattern were established 3,8,[10][11][12][13][14][15][16][17][18][19][20][21][22] . In this context, Meier et al were able to express the dependence of the longest wavelength of absorption (λ max ) on chain length for donor-acceptor substituted polyacetylene 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da langkettige Dialkylamino-Reste gute Solubilisierungseigenschaften haben, konnte eine systematische Studie mit den Oligo(1,4-phenylenvinylenen) (OPV) 5 a-e, 6 a-e, 7 a-e und 8 a-e durchgeführt werden. [21,25] Ausgehend von 9 wurde zunächst mithilfe der WittigHorner-Reaktion und einer einfachen Schutzgruppentechnik die Reihe 5 c-8 c aufgebaut (Schema 5), wobei das Phosphonat 10 als "Verlängerungsreagens" fungierte. Nach der basischen Kondensation erfolgte unmittelbar bei der sauren Aufarbeitung die Entschützung der von 10 eingebrachten Abbildung 3.…”
Section: Langwellige Elektronenübergänge In Konjugierten Oligomerenunclassified